FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2016-2018 - Rini Cahyanti; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
Abstract               This research was conducted to examine the effect of variable Earning Per Share (EPS), Price Earning to Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER), Return On Assets (ROA), and Return On Equity ( ROE) to Stock Return. The sampling technique used was purposive sampling with the criteria (1) the company was listed on the Indonesia Stock Exchange and registered as an LQ45 company in the 2016-2018 period, (2) The company must be listed in the LQ45 index continuously (constant) for 3 years starting from the period 2016-2018, (3) LQ45 companies for the 2016-2018 period have reported financial statements that include the values of the variables to be studied (4) Financial reports using the rupiah currency. Obtained a total sample of 45 from 45 companies for 3 years. The analysis technique used is multiple regression analysis and hypothesis testing with partial t test and simultaneous F test, with a significance level of 5%. From the results of this analysis, it is found that simultaneously there is a significant influence between EPS, PER, PBV, DER, ROA, and ROE on LQ45 Company Stock Return, but the effect is very small, only 51.8%. While partially, only the DER, ROA and ROE factors have a significant effect on LQ45 Company Stock Return with a value of less than 5%. Keyword: Earning Per Share (EPS), Price Earning to Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER), Return On Assets (ROA), and Return On Equity ( ROE) and Stock Return